Characterization of small HSPs from Anemonia viridis reveals insights into molecular evolution of alpha crystallin genes among cnidarians. - Aldo Nicosia (Public Library of Science (PLoS), 2014)
Gene family encoding small Heat-Shock Proteins (sHSPs containing α-crystallin domain) are found both in prokaryotic and eukaryotic organisms; however, there is limited knowledge of their evolution. In this study, two small HSP genes termed AvHSP28.6 and AvHSP27, both organized in one intron and two exons, were characterised in the Mediterranean snakelocks anemone Anemonia viridis. The release of the genome sequence of Hydra magnipapillata and Nematostella vectensis enabled a comprehensive study of the molecular evolution of α-crystallin gene family among cnidarians. Most of the H. magnipapillata sHSP genes share the same gene organization described for AvHSP28.6 and AvHSP27, differing from the sHSP genes of N. vectensis which mainly show an intronless architecture. The different genomic organization of sHSPs, the phylogenetic analyses based on protein sequences, and the relationships among Cnidarians, suggest that the A.viridis sHSPs represent the common ancestor from which H. magnipapillata genes directly evolved through segmental genome duplication. Additionally retroposition events may be considered responsible for the divergence of sHSP genes of N. vectensis from A. viridis. Analyses of transcriptional expression profile showed that AvHSP28.6 was constitutively expressed among different tissues from both ectodermal and endodermal layers of the adult sea anemones, under normal physiological conditions and also under different stress condition. Specifically, we profiled the transcriptional activation of AvHSP28.6 after challenges with different abiotic/biotic stresses showing induction by extreme temperatures, heavy metals exposure and immune stimulation. Conversely, no AvHSP27 transcript was detected in such dissected tissues, in adult whole body cDNA library or under stress conditions. Hence, the involvement of AvHSP28.6 gene in the sea anemone defensome is strongly suggested.